Analysis of the Floating Net Cage Business for Tilapia (Oreochromis niloticus) at Lake Maninjau Nagari Tanjung Sani, Tanjung Raya District, West Sumatra Province - Harahap, Stepandi; Hendrik, Hendrik; Yanti, Chicka Willy (Jurnal Perikanan dan Kelautan, 2024)
Lake Maninjau has been developed with the floating net cage (KJA) system for aquaculture. In 2020, the number of KJA decreased by 0,03%, but in 2021, the number of KJA increased by 9,5%; this shows that the cultivator community still maintains the tilapia KJA business. This situation makes the author want to know the investment amount, income, and business. This situation makes the author want to know the investment amount, income, and business feasibility. The method used was a survey, while the respondents were determined deliberately on five KJA cultivators with ten bags and five KJA cultivators with 20 bags. The results showed that the KJA with ten bags had an investment of IDR 626,864,000, an IDR 825,600,000/year income, and an IDR 227,346,334/ year profit. Meanwhile, KJA has 20 bag units, an investment of IDR 1,276,100,000, an income of IDR 1,684,800,000/year, and IDR 490,695,668/ year. Based on the analysis results, the investment criteria were obtained for KJA with 10 RCR bag units (1.38), FRR (36.26), PPC (2.76) and for KJA with 20 RCR bag units (1.41), FRR (38, 45), PPC (2.60). The calculation of the RCR is more than 1, the FRR is greater than the BRI bank interest rate of 6.4%, the PPC is less than the maximum time required, and the economic life of the equipment used for the tilapia KJA business is two years and seven months, then the KJA fish business tilapia worth to run.